4 Clinical features and outcomes of childhood hypertrophic cardiomyopathy: a retrospective study in the united kingdom. (2nd February 2018) - Norrish, G; Field, E; ,; Kaski, JP
Abstract : Purpose: Describe the clinical features and outcomes of Childhood Hypertrophic Cardiomyopathy (HCM) in a national cohort. Methods: A retrospective, multi-centre cohort of children diagnosed with HCM in the United Kingdom (UK) since 1980 was formed from 12 paediatric cardiac centres. Anonymised, non-invasive clinical data were collected. Results: 705 patients with childhood HCM were identified with a median age at presentation of 5 years (range 0–16). 21% (n=149) of patients presented during infancy. The underlying aetiology was varied including idiopathic (n=450, 63.8%), Noonan's syndrome (n-121, 17.2%), Friedreich's ataxia (n=60, 8.5%) and inborn errors of metabolism (n=63, 8.9%). Those presenting under 1 year of age were more likely to have a diagnosis of Noonan's syndrome (39% vs 11.3%, p=0.000*) or inborn error of metabolism (18% vs 0.9% p=0.000*). The majority of patients were asymptomatic, in NYHA/Ross class I at presentation (n=535, 76%), however heart failure symptoms were more common in infants (13% vs 3%, p=0.000*). A history of unexplained syncope (n=41, 5.8%) or previous aborted cardiac arrest (n=14, 3.4%) was uncommon. Overall the prognosis was good, survival without death or transplant was 91.7% (93.7–96.8) at 5 years. Children diagnosed during infancy or with an inborn error of metabolism had a worse prognosis with a survival of 81% and 82% at 1 year respectively. Conclusion: This national study of childhood HCM describes a heterogeneous cohort whose outcomes are dependent on underlying aetiology and age of presentation. Further studies are needed to systematically investigate risk factors for prognosis in this patient group.